Breast cancer-derived microparticles display tissue selectivity in the transfer of resistance proteins to cells. - Ritu Jaiswal; Frederick Luk; Penelope V Dalla; Georges Emile Raymond Grau; Mary Bebawy (PLoS ONE, 2013)
Microparticles (MPs) play a vital role in cell communication by facilitating the horizontal transfer of cargo between cells. Recently, we described a novel "non-genetic" mechanism for the acquisition of multidrug resistance (MDR) in cancer cells by intercellular transfer of functional P-gp, via MPs. MDR is caused by the overexpression of the efflux transporters P-glycoprotein (P-gp) and Multidrug Resistance-Associated Protein 1 (MRP1). These transporters efflux anticancer drugs from resistant cancer cells and maintain sublethal intracellular drug concentrations. By conducting MP transfer experiments, we show that MPs derived from DX breast cancer cells selectively transfer P-gp to malignant MCF-7 breast cells only, in contrast to VLB100 leukaemic cell-derived MPs that transfer P-gp and MRP1 to both malignant and non-malignant cells. The observed transfer selectivity is not the result of membrane restrictions for intercellular exchange, limitations in MP binding to recipient cells or the differential expression of the cytoskeletal protein, Ezrin. CD44 (isoform 10) was found to be selectively present on the breast cancer-derived MPs and not on leukaemic MPs and may contribute to the observed selective transfer of P-gp to malignant breast cells observed. Using the MCF-7 murine tumour xenograft model we demonstrated the stable transfer of P-gp by MPs in vivo, which was found to localize to the tumour core as early as 24 hours post MP exposure and to remain stable for at least 2 weeks. These findings demonstrate a remarkable capacity by MPs to disseminate a stable resistant trait in the absence of any selective pressure.